Autotandem Catalysis: Inexpensive and Green Access to Functionalized Ketones by Intermolecular Iron‐Catalyzed Amidoalkynylation/Hydration Cascade Reaction via N‐Acyliminium Ion Chemistry. Issue 62 (4th October 2021) - Abdallahi, Sidi Mohamed; Ewies, Ewies F.; El‐Shazly, Mohamed; Ould Elemine, Brahim; Hadou, Abderrahmane; Moncol, Ján; Lawson, Ata Martin; Daich, Adam; Othman, Mohamed
Abstract: Iron‐based catalysts were applied in cascade‐type reactions for the synthesis of different carbonyl compounds. The reactions proceeded by a new iron‐catalyzed cascade of alkynylation/hydration by using both the σ‐ and π‐Lewis acid properties of iron salts. The alkynylation reactions of several endo and exocyclic acetoxylactams were achieved with three different catalysts including FeCl3  ⋅ 6H2 O, FeCl3, and Fe(OTf)3 showing the efficiency of σ‐Lewis acidity of iron (III) salts in catalyzing the alkynylation reaction. We also demonstrated that the reaction sequence could be shortened by the direct use of hydroxylactams, leading to an environmentally friendly protocol, avoiding the need to perform unnecessary lengthy steps. A combination of the hard/soft iron Lewis acid properties was then used to implement an unprecedented tandem intermolecular alkynylation/intramolecular hydration sequence allowing expedient access to a new carbonyl structures from trivial materials. Abstract : Autotandem catalysis : Iron(III) catalysts were shown to efficiently catalyze intermolecular alkynylation reactions of various alkoxy, acetoxylactams, and hydroxylactams. This chemistry broadens the scope of iron catalysis by highlighting new aspects of iron salts σ‐Lewis acidity. More importantly, this approach is amenable to an unprecedented tandem intermolecular alkynylation/intramolecular hydration sequence affording expedient access to a new carbonyl structures.